Performance evaluation of students' hostel of the college of Agriculture and Environmental Science Kaduna State University, Nigeria - Aminat Idowu Ibiyeye; Nghai Ezekiel Suleman; Kasham J. Shamang; D. Shebanyan Duniya; Lamba Adamu (Springer, 2024)
Abstract Global higher education aims to develop students' intellectual capacities, foster personal growth, and mold behaviors, thoughts, and creativity for a fulfilling life. Within this framework, university residential spaces play a vital role in advancing these objectives. A well-designed hostel, tailored to students' needs and comfort, promotes shared interests and positive educational outcomes. Therefore, the importance of satisfactory residential facilities in improving students' performance should not be underestimated. This research examined the satisfaction levels of current residents of the College of Agriculture and Environmental Science hostel at Kaduna State University (KASU) regarding their accommodation. It also explored variations in satisfaction among groups with different socio-demographic characteristics. The study focused on two performance requirements for the evaluation of students' satisfaction, namely, the technical performance requirement (thermal comfort, acoustical comfort, visual comfort, indoor air quality, and fire safety) and the functional performance requirement (interior and exterior finish systems, room layout, support services, efficiency of circulation, and proximity to other facilities on campus). A total of forty-eight (48) performance indicators from the two performance requirement were evaluated through a survey questionnaire. The findings indicated that students generally expressed dissatisfaction across all performance elements, except thermal comfort and indoor air quality, room layout and size, efficiency of circulation, and proximity to facilities. The significance of this study lies in its potential to inform targeted improvements and interventions that enhance student satisfaction, comfort, and overall experience within university hostel accommodations. Findings from this study will contribute to creating a more supportive, enjoyable and conducive living environment for students, ultimately promoting their well-being and academic success.